Forestry Programmes - Need for Change in Approach - Khullar, Pankaj (Indian Forester, 1992)
Forestry in India today is no longer the forestry that was practiced till about two decades ago. Afforestation schemes, national as well as donor sponsored, aimed at ameliorating the wood shortage in the country, are in and the old concepts of production/protection forestry are out. Whether or not forestry will become a People's programme will depend to a large extent on motivating the rural masses and carrying them along. Experience gained so far shows that there has been a general lack of sufficient groundwork and socio-economic studies before forestry projects have been launched, leading to failures insofar as the achievement of objectives is concerned. Foresters will have to change their entire attitude towards forestry in general, and community forestry in particular, if they are to bring about any lasting change in the attitudes and approaches of the target groups, the rural masses.